Inventura knjižničnega gradiva v splošni knjižnici z uporabo sistema COBISS - Berginc, Jerneja (Knjižnica, 2020)
Besides the collective role of the library catalogue, by using technology it has also be-co me important equipment for simplified searching within the library collection by library users. Being in order, the catalogue reflects a qualitative library, and it can con-tribute to a satisfying user experience. COMARC/H architecture, among other functions, provides a unified way of recording the quantity and location of the library stock within the library catalogue. The article points out the basic meaning of regularity of the data, put into the library catalogue, and also the meaning of professional knowledge and workplace responsibility at every point of work in the library, that results in a qualita-tive library catalogue. The library collection stocktaking as a part of the supervision is being placed into the process of library collection management, which, if done regu-larly, brings out a relevant and user-friendly library collection. The article shows the procedure of the library collection stocktaking using COBISS3/Inventura software archi-tecture, used in a small public library. There are also some results of the library collec-tion stocktaking added, showing a very small share of actually missing items.
Keywords: COBISS; inventura; knjižnično gradivo; splošne knjižnice